Peran Perpustakaan Digital dalam Proses Pembelajaran Digital Natives: Studi Literatur melalui Garuda - Wahhaj, Ikhsan Sirojul; Anwar, Rully Khairul; Rukmana, Evi Nursanti (Media Pustakawan, 2025)
The transformation of conventional libraries into digital libraries has resulted in many significant changes, especially in the generation of digital natives to access information. This research aims to analyze the role of digital libraries in supporting the learning process of the digital natives generation, which refers to the Garuda database-indexed literature review. This research uses a narrative literature review method by analyzing various references to find new knowledge. The number of references analyzed in this study amounted to 15 references out of a total of 30 references taken from the Garuda database with a range of years from 2015 to 2024. Researchers used the Garuda database because it has the advantage of easy access to articles and many articles from Indonesia are of high quality and free. The results and discussion show that digital libraries have an important role in supporting the learning process of the digital natives generation. First, digital libraries play a role in providing digital literacy education for digital natives so that the search for information needed is relevant, valid, and can be utilized properly. Second, digital libraries play a role in providing complete, quality, and easily accessible online collections anytime and anywhere. Third, digital libraries play a role in providing responsive services to digital natives such as email, Instagram, and website services. In carrying out this role, librarians who understand digital libraries and can meet the information needs of digital natives are needed.